Oil palm frond juice as future fermentation substrate: a feasibility study - Che Maail, Che Mohd Hakiman; Ariffin, Hidayah; Hassan, Mohd Ali; Md Shah, Umi Kalsom; Shirai, Yoshihito (Hindawi Publishing Corporation, 2014)
Oil palm frond (OPF) juice is a potential industrial fermentation substrate as it has high sugars content and the OPF are readily available daily. However, maximum sugars yield and storage stability of the OPF juice are yet to be determined. This study was conducted to determine the effect of physical pretreatment and storage duration of OPF petiole on sugars yield. Storage stability of OPF juice at different storing conditions was also investigated. It was found that OPF petiole squeezed by hydraulic pressing machine gave the highest sugars recovery at almost 40 g/kg, accounting for a recovery yield of 88%. Storage of OPF petiole up to 72 hrs prior to squeezing reduced the free sugars by 11 g/kg. Concentrated OPF juice with 95% water removal had the best storage stability at both 4 and , when it was stored for 10 days. Moreover, concentrated OPF syrup prepared by thermal processing did not give any Maillard effect on microbial growth. Based on our results, OPF juice meets all the criteria as a good fermentation substrate as it is renewable, consistently available, and easy to be obtained, it does not inhibit microbial growth and product formation, and it contains no impurities.